Influence of Leaf Harvest on Seed Yield in Cowpea - Alladoum, Ange Ndogonoudji; Adoum, Dona; Antoine, Nassourou Maina; Noubissie, Jean Baptiste Tchiagam (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
The purpose of this study is to determine the period when leaf removal has less impact on pod production. The effect of defoliation on pod production was verified on three pure lines grown in the field. Cowpea is consumed from the seedling stage to the harvest (seedling, young leaves, young pods, immature pods, dry pods) and is used in several African dishes. In the Sudano-Sahelian zone of Chad, cereals are the basis of food. The diversification of this diet requires the introduction of foods rich in protein and minerals and justifies the quantitative improvement of the leaves and seeds of cowpeas. The experimental device is a split plot with three repetitions with the three genotypes that constitute the main treatments and the nine modes of defoliation. The analysis of variance in the collection data shows a significant difference between the average number of leaves per plant and the number of pods per plant depending on the number of leaf samples (p<0.05). The removal of 5 leaves at 40 days after emergence stimulates pod production. This stage seems to be the ideal stage of sampling. Flowers and immature pods require a maximum of nutrients during flowering and fruiting, and leaf sampling, the seat of synthesis of these nutrients, results in a decrease in the distribution of nutrients. The elaborate sap causes the fall of newly formed flowers and pods. Removing the leaves at this stage would allow farmers to have plenty of leaves and seeds in order to diversify their diet and in turn fight against malnutrition. However, this be extended to other agroecological, soil, and climatic conditions and include other varieties before generalizing.